Research on Robust Algorithm of Color Holographic Watermark Based on DCT-DWT - Li, S K; Wang, A L; Pang, J P; Guo, L; Xin, K; Fan, S X; Liu, F P (IOP conference series. Materials Science and Engineering, 2019)
Based on the DCT-DWT algorithm, a new method for embedding color holographic watermarks into color carrier images is proposed. The color watermark image and the color carrier image are divided into three channels: R, G, and B. The hologram is generated for each channel's watermark image by a four-step phase shift method, and the hologram is subjected to Arnold transformation. The carrier image is decomposed by first-order wavelet, the watermark embedding space is changed from spatial domain to transform domain, low-frequency components are extracted and segmented, the scrambled holographic watermark images are respectively sub-channel embedded in the carrier image by discrete cosine transform. The experimental results show that the algorithm is robust and can resist some conventional attacks. In this algorithm, the watermark image is transformed into a hologram, which increases the difficulty of decryption.